2013
DOI: 10.1159/000351266
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of Microvascular Decompression for the Treatment of Hemifacial Spasm in the Elderly

Abstract: Background: Hemifacial spasm (HFS) is a common disorder and has a significant impact on the quality of life. Microvascular decompression (MVD) is an effective and safe treatment option for patients with HFS, however the effectiveness and safety of MVD in elderly patients with HFS is not clear. Methods: We enrolled 699 HFS patients who underwent MVD from February 2008 to December 2011 at the Samsung Medical Center in Seoul, Korea. Subjects were divided into two groups: an elderly group (patients who were 60 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Tinnitus tends to correlate with HL, and patients will often complain of the ringing more than their HL. 21,22 Since tinnitus often resolves in conjunction with HL, it is also appropriate to wait at least 2 months postoperatively before any intervention is pursued.…”
Section: Discussionmentioning
confidence: 99%
“…Tinnitus tends to correlate with HL, and patients will often complain of the ringing more than their HL. 21,22 Since tinnitus often resolves in conjunction with HL, it is also appropriate to wait at least 2 months postoperatively before any intervention is pursued.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, when we compared clinical features between elderly patients with HFS and younger patients in a previous study, the elderly patients with HFS showed more severe-spasms and were more likely to have HTN and DM. 18 Considering that the age at MVD was not associated with spasm severity in the multivariate analysis performed in the present study, the severity of HFS might not be directly related to age, but rather to other conditions such as HTN or disease duration. Previous studies have also focused on the association between vascular dolichoectasia and HFS, concluding that dolichoectasia is usually associated with HTN.…”
Section: Discussionmentioning
confidence: 49%
“… 11 12 13 33 This discrepancy can be attributed to the effects of various factors including age, disease duration, comorbidities, and psychologic status on surgical outcomes and complications. 9 18 Although we observed that facial palsy was delayed in the severe-spasm group, the complication rate was still low and so MVD could be an effective treatment option for patients with HFS. Since treatment modalities are selected and complications are predicted based on clinical or laboratory findings, rather than on intraoperative findings, more studies focusing on the clinical features of HFS—like the present study—are important for providing doctors with the best information possible for making appropriate decisions.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Injuries to the vestibulocochlear nerve or inner ear vasculature can also result in potentially disabling postoperative tinnitus. Tinnitus tends to correlate with hearing loss, and patients will often complain of the ringing more than their hearing loss [21,22]. Since tinnitus often resolves in conjunction with hearing loss, it is also appropriate to wait at least two months postoperatively before any intervention is pursued.…”
Section: Discussionmentioning
confidence: 99%